2021
DOI: 10.3389/fnut.2020.610946
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Flavonifractor plautii, a Bacteria Increased With Green Tea Consumption, Promotes Recovery From Acute Colitis in Mice via Suppression of IL-17

Abstract: Flavonifractor plautii (FP) has been reported to participate in the metabolism of catechins in the human gut. However, there is limited information on the immune regulatory effects of this bacterium. We confirmed that the administration of green tea increases the abundance of FP in the gut microbiota and investigated the effect of FP in a mouse colitis model. Mice were orally administered FP for 10 consecutive days; colonic inflammation was evaluated daily on the basis of stool consistency, gross rectal bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…Additionally, an elevation of genus Flavonifractor was associated with depression, symptom severity, or worse physical functioning, with no contradictory results [ 42 , 44 , 48 , 64 , 77 ]. Even though Flavonifractor plautii was recently found to suppress the immune response in mice in multiple studies conducted by the same research group [ 101 , 102 , 103 ], it was repeatedly associated with several diseases, including ulcerative colitis, autoimmune diseases, obesity, and even with a poor diet [ 104 , 105 ]. Our findings of elevated Flavonifractor , with no study finding opposite results, strongly support its negative influence on the host’s health, including affective disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, an elevation of genus Flavonifractor was associated with depression, symptom severity, or worse physical functioning, with no contradictory results [ 42 , 44 , 48 , 64 , 77 ]. Even though Flavonifractor plautii was recently found to suppress the immune response in mice in multiple studies conducted by the same research group [ 101 , 102 , 103 ], it was repeatedly associated with several diseases, including ulcerative colitis, autoimmune diseases, obesity, and even with a poor diet [ 104 , 105 ]. Our findings of elevated Flavonifractor , with no study finding opposite results, strongly support its negative influence on the host’s health, including affective disorder.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, in addition to the existing lactic acid bacteria and Bifidobacterium , a wider range of microorganisms are expected to be used in the future, and these microorganisms are referred to as next-generation probiotics ( 34 ). For example, it was reported that Flavonifractor plautii , a bacterium isolated from human intestine, improved inflammation ( 35 , 36 ) and allergic immune responses ( 37 ). In addition, in recent studies, genetically modified lactic acid bacteria have been constructed to attenuate cancer ( 38 ), inflammation ( 39 , 40 ), obesity ( 41 ), and allergy ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonifractor spp. have also been reported to increase with green tea consumption and promote recovery from acute colitis in mice 44 . Veillonella spp.…”
Section: Discussionmentioning
confidence: 96%